Coupling free radical catalysis, climate change, and human health. Issue 16 (11th April 2018) - Anderson, J. G.; Clapp, C. E.
Abstract : Linking free radical catalytic loss of stratospheric ozone over the central United States to climate forcing by CO2 and CH4 . Abstract : We present the chain of mechanisms linking free radical catalytic loss of stratospheric ozone, specifically over the central United States in summer, to increased climate forcing by CO2 and CH4 from fossil fuel use. This case directly engages detailed knowledge, emerging from in situ aircraft observations over the polar regions in winter, defining the temperature and water vapor dependence of the kinetics of heterogeneous catalytic conversion of inorganic chlorine (HCl and ClONO2 ) to free radical form (ClO). Analysis is placed in the context of irreversible changes to specific subsystems of the climate, most notably coupled feedbacks that link rapid changes in the Arctic with the discovery that convective storms over the central US in summer both suppress temperatures and inject water vapor deep into the stratosphere. This places the lower stratosphere over the US in summer within the same photochemical catalytic domain as the lower stratosphere of the Arctic in winter engaging the risk of amplifying the rate limiting step in the ClO dimer catalytic mechanism by some six orders of magnitude. This transitions the catalytic loss rate of ozone in lower stratosphere over the United States in summer from HOx radical control to ClOx radical control, increasing the overall ozone loss rate by some two orders of magnitude over that of the unperturbed state. Thus we address, through a combination of observations and modeling, the mechanistic foundation defining why stratospheric ozone, vulnerable to increased climate forcing, is one of the most delicate aspects of habitability on the planet.